Perbandingan Pengelolaan Infrastruktur Transportasi Darat di Indonesia dan Jepang - Lala Amalia Marcelina; Ade Hani Puspa Dewi; Irdan Suwardana Yahya; Kaila Zalfa Alisha; Mawar Mawar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Land transportation infrastructure is an important component in supporting public mobility and national economic growth. This research aims to compare the management of land transportation infrastructure in Indonesia and Japan by highlighting the differences in strategies, policies, and innovations implemented in each country. The method used is a literature study with a qualitative approach that examines policy documents, institutional reports, and previous research. The results show that Japan has built an integrated and efficient land transportation system through long-term planning and high-tech support, while Indonesia still faces challenges in infrastructure equity, governance, and rapid urbanization. However, Indonesia is starting to show progress through national strategic projects, service digitization, and technological cooperation with Japan. The implication of this study confirms that improving the quality of governance, fairer distribution of infrastructure investment, and integration of technology in the transportation system are not only important, but are key prerequisites for Indonesia to realize an efficient, inclusive, and sustainable transportation system. In addition, lessons learned from Japanese practices show that collaboration among stakeholders, regular evaluation of policies, and long-term planning need to be part of the land transportation reform framework in Indonesia.